New methods in 18F-fluorination and fluoroalkylation - Ford, J (2024)
Chapter 1 (Introduction) summarises the key concepts surrounding Positron Emission Tomography (PET) imaging, including the underlying physical principles and its applications and the use of fluorine-18 as a PET radioisotope. A brief account of fluorine-18 radiochemistry, including the 18F-fluorination of aliphatic and aromatic scaffolds, as well as 18F-fluoroalkylation chemistry is also provided. The chapter concludes with an outline of the work disclosed in this thesis.